Pengaruh Kombinasi Manual Traksi Dan Isometrik Quadricep Terhadap Pengurangan Nyeri Gerak Pada Pasien Osteoarthritis Genu Grade III Di RS Mitra Keluarga Waru - Paskalis Sumarah Ing Widi; Achmad Fariz; Retno Dewi Prisusanti; Agung Hadi Endaryanto (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2021)
Background: Grade III Genu osteoarthritis is one of the classifications of genu osteoarthritis characterized by pathological changes throughout the joint structure, and is also a joint disease that usually occurs in weight-loss joints characterized by narrowing of joint gaps, and decreased muscle strength around the joint that causes pain when moving. Objective: To analyze the effect of the combination of Manual Traction and Isometric Quadricep on the decrease in acuteness of motion pain of Osteoarthritis Genu Grade III patients. Methods: The method in this study is a type of quasi experiment through using data processing that uses pre test as data before receiving treatment and post test after receiving the treatment (one group pre-test post-test). The population in this study is a patient of Mitra Keluarga Waru Sidoarjo Hospital as many as 60 people with a sample of 30 people. Sample selection uses inclusion and exclusion criteria. The study used the VAS-P (Visual Analogue Scale for Pain) instrument. The data was then statistically analyzed with the Chi Square test with a p value of <0.05. Results: Chi Square test results obtained there was an effect of a combination of Manual Traction and Isometric Quadricep on the decrease in actual pain movement of Osteoarthritis Genu Grade III patients with a value of 0.001. Conclusion: The combination of Manual Traction and Isometric Quadricep may decrease the actuality of motion pain of Grade III Osteoarthritis Genu patientsKeywords: osteoarthritis genu grade III; manual traction; isometric quadricep; visual analogue scale for pain; painABSTRAK Latar belakang: Osteoarthritis Genu Grade III merupakan salah satu klasifikasi dari osteoarthritis genu yang ditandai dengan perubahan patologis di seluruh struktur sendi, dan juga merupakan penyakit persendian yang biasanya terjadi pada sendi yang menumpu berat badan yang ditandai dengan adanya penyempitan celah sendi, dan penurunan kekuatan otot disekitar sendi yang menyebabkan nyeri saat bergerak. Tujuan: Untuk menganalisa pengaruh pemberian kombinasi Manual Traction dan Isometric Quadricep terhadap penurunan akutualitas nyeri gerak pasien Osteoarthritis Genu Grade III. Metode: Metode pada penelitian ini yakni jenis quasi eksperimen melalui menggunakan pengolahan data yaitu menggunakan pre test sebagai data sebelum menerima perlakuan dan post test sesudah menerima perlakuannya (one group pre-test post-test). Populasi dalam penelititan ini adalah pasien RS Mitra Keluarga Waru Sidoarjo sebanyak 60 orang dengan sampel 30 orang. Pemilihan sampel menggunakan kriteria inklusi dan eksklusi. Penelitian ini menggunakan instrument VAS-P (Visual Analogue Scale for Pain). Data kemudian dianalisis secara statistik dengan uji Chi Square dengan p value <0,05. Hasil: Hasil uji Chi Square didapatkan ada pengaruh kombinasi Manual Traction dan Isometric Quadricep terhadap penurunan aktualitas nyeri gerak pasien Osteoarthritis Genu Grade III dengan p value = 0,001. Kesimpulan: Kombinasi Manual Traction dan Isometric Quadricep dapat menurunkan aktualitas nyeri gerak pasien Osteoarthritis Genu Grade IIIKata kunci: osteoarthritis genu grade III; manual traction;isometric quadricep; visual analogue scale for pain; nyeri